(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This study aims to analyze the SWOT, IFE, and EFE of Muhammadiyah Schools in Bengkulu City. The study was conducted at Muhammadiyah Schools in Bengkulu City from September to November 2023. The research methodology used includes quantitative and qualitative approaches. Quantitatively, data was obtained by distributing questionnaires via Google Form to 54 respondents and qualitatively conducting interviews with 4 respondents representing elements of Muhammadiyah education figures, Aisyiyah, lecturers, and Muhammadiyah teachers. The results of the study indicate that: 1) There are 10 indicators of strength, 9 indicators of weakness, 6 indicators of opportunity, and 5 indicators of threat in Muhammadiyah schools, and there are 12 SO, WO, ST, and WT strategies that can be applied for the progress and development of Muhammadiyah school education, 2) The value of internal factor analysis (IFE) is 2.85 with a moderate category, and the value of external factor analysis (EFE) is 2.6 with a moderate category, and 3) Muhammadiyah schools in Bengkulu city from kindergarten, elementary school/MMI, junior high school/MMTS, and senior high school/MMA are in quadrant V, namely in a condition of maintaining and maintaining. The recommended strategy for the progress and development of Muhammadiyah schools is a strategy that is aggressively penetrating the community to convince the general public that Muhammadiyah schools can be the main choice, and also a strategy for developing Muhammadiyah schools into superior schools is needed through curriculum changes, radical changes in the school’s vision and mission, and improvements in internal quality, both human resources and related infrastructure.